Establishing a xenograft mouse model of peritoneal dissemination of gastric cancer with organ invasion and fibrosis. Issue 1 (December 2017) - Okazaki, Mitsuyoshi; Fushida, Sachio; Harada, Shinichi; Tsukada, Tomoya; Kinoshita, Jun; Oyama, Katsunobu; Miyashita, Tomoharu; Ninomiya, Itasu; Ohta, Tetsuo
Abstract Background The clinical prognosis of gastric cancer with peritoneal dissemination is poor because of its chemoresistance and rich fibrosis. While several gastric cancer cell lines have been used to establish models of peritoneal dissemination by intraperitoneal injection, most peritoneal tumors that form adopt a medullary pattern in microscopic appearance. This histological finding for the model differs from that in the clinical situation. This study was performed to demonstrate the contribution of human peritoneal mesothelial cells (HPMCs) to fibrotic tumor formation and to establish a new xenograft model with high potential for peritoneal dissemination with organ invasion and extensive fibrosis. Methods We established four types of xenograft model: i) intraperitoneal injection of MKN45-P cells alone (control group), ii) injection of MKN45-P cells co-cultured with HPMCs (co-cultured group), iii) scratching the parietal peritoneum (parietal group), and iv) scratching the visceral peritoneum (visceral group) with a cotton swab before injection of co-cultured cells. Fibrosis, α-smooth muscle actin expression, and organ invasion by tumor cells were all assessed by immunohistochemical examination. Results All mice developed abdominal swelling with peritoneal tumors and bloody ascites. Tumors of the control and co-cultured groups were not invasive or fibrotic. Contrastingly, tumors of the scratch groups exhibited rich stromal fibrosis and possessed increased α-smooth muscle actin (α-SMA) expression. In particular, the visceral group showed edematous and spreading tumors invading the intestinal wall. Conclusion We established a model of peritoneal dissemination with organ invasion and stromal fibrosis. Formation of peritoneal dissemination required a favorable environment for cell adhesion, invasion, and growth. This model may be useful for analyzing the pathogenesis and treatment of peritoneal dissemination of gastric cancer.